PENYULUHAN HUKUM PERLINDUNGAN DATA PRIBADI DI SUB DIREKTORAT HUKUM KORPORAT PT PLN (PERSERO) - Rama Dhianty (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
One of the challenges faced by PT PLN(Persero) as a State-Owned Electricity Company, isthe phenomenon of technological disruption. In linewith this, currently PT PLN (Persero) has digitized itsgeneration, transmission and distribution operations,as well as digitized customer service. Digitalization ofcustomer service is carried out by PT PLN (Persero)by launching the New PLN Mobile application onDecember 18, 2020. PLN customers through the NewMobile PLN application can access all services viasmartphones. The launch of New PLN Mobileultimately made PLN an Electronic System Operator.Based on Government Regulation Number 71 of 2019concerning the Implementation of Electronic Systemsand Transactions, PLN as an Electronic SystemOperator has obligations, especially obligationsrelated to the management, processing, storage andguarantee of customer personal data protection. Theactivity called